2016
DOI: 10.3136/fstr.22.403
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Proanthocyanidins Extract Prevents Cisplatin-induced Cardiotoxicity in Rats

Abstract: Cisplatin-treated rats experienced a significant elevation of serum activities of lactate dehydrogenase (LDH), aspartate transaminase (AST), alanine transaminase (ALT) and creatine kinase (CK). These effects were accompanied by significant increases in the levels of malondialdehyde (MDA) and nitric oxide (NO), and decreases in the glutathione (GSH) content, and the activities of glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD) in cardiac tissues. Pathological examination revealed that cisplatin c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Comprising a mix of bioflavonoids with biological activity (e.g., oligomeric proanthocyanidins), GSPE can have protective effect against hypertrophy and cellular infiltrations of cardiac muscle fibre cells caused by EST by diminishing the levels of free radicals and lipid peroxidation. From this perspective, the study concurred not only with Razmaraii et al [46], who found that GSPE protected against cardiotoxicity caused by doxorubicin in Wistar rats, but also with Lian et al [47], who observed that cardiotoxicity, lipid peroxidation, oxidative stress, and cardiac damage caused by cisplatin were alleviated by GSPE.…”
Section: Discussionsupporting
confidence: 81%
“…Comprising a mix of bioflavonoids with biological activity (e.g., oligomeric proanthocyanidins), GSPE can have protective effect against hypertrophy and cellular infiltrations of cardiac muscle fibre cells caused by EST by diminishing the levels of free radicals and lipid peroxidation. From this perspective, the study concurred not only with Razmaraii et al [46], who found that GSPE protected against cardiotoxicity caused by doxorubicin in Wistar rats, but also with Lian et al [47], who observed that cardiotoxicity, lipid peroxidation, oxidative stress, and cardiac damage caused by cisplatin were alleviated by GSPE.…”
Section: Discussionsupporting
confidence: 81%
“…The results of the present study were confirmed by the results of Al-Sowayan [61] who reported that rats injected with DOX showed a significant (P<0.05) increase the level of MDA compared to the control groups.GSPE (200 mg/kg/day) along with DOX significantly caused an improvement in MDA and this may be due to the polyphenolic content of GSPE which scavenge free radicals and act as good antioxidants against lipid peroxidation in the phospholipid bilayer [62]. Also, Lian et al [53] showed that myocardial MDA level of lipid peroxidation was significantly increased in the cisplatin administered group, comparing to control group (P < 0.05), however the administration of GSPE reduced MDA level in heart tissues with a significant milder pathological change caused by cisplatin. These observations indicated that GSPE had protective effect on cisplatin induced oxidative stress in cardiac tissue.…”
Section: Serum Malondialdehyde (Mda) and Total Antioxidant Capacity (Tac) In Experimental Groupsmentioning
confidence: 98%
“…This indicated that treatment with GS and MP extracts caused an improvement of CP toxicity and these results were confirmed by microscopic examination of heart and liver tissue which cause improvement in heart and liver tissue. [53].…”
Section: Cardiac and Hepatic Function Enzymes In Experimental Groupsmentioning
confidence: 99%
“…The subsequent DNA produced starts apoptosis. Study demonstrated the cardiotoxic response of cisplatin may cause electrocardiographic changes, toxic effect of free radicals, mitigate the lipid peroxidation which was diminished by concentrate of grape seed proanthocyanidins (Lian et al, 2016). Expanded oxidative stress and histopathological injury have been involved in the cardiotoxicity that constrains the clinical Page 14 / 23 use of cisplatin (CP) as an anti-cancer drug which was then analysed by managing cisplatin administration after treatment by hesperidin (Oguzturk et al, 2016).…”
Section: Cisplatinmentioning
confidence: 99%